Synergistic effects of mechanical stimulation and crimped topography to stimulate natural collagen development for tendon engineering. (June 2022) - Chen, Zhenying; Zhou, Boya; Wang, Xiansong; Zhou, Guangdong; Zhang, Wenjie; Yi, Bingcheng; Wang, Wenbo; Liu, Wei
Abstract: Suitable scaffold structures and mechanical loading are essential for functional tendon engineering. However, the bipolar fibril structure of native tendon collagen is yet to be recaptured in engineered tendons. This study compared the development of Achilles tendons of postnatal rats with and without (via surgical section) mechanical loading to define the mechanism of mechanical stimulation-mediated tendon development. The results demonstrated that the severed tendons weakened mechanically and exhibited disorganization without a bipolar fibril superstructure. Proteomic analysis revealed differentially expressed key regulatory molecules related to the collagen assembly process, including decreased fibromodulin, keratocan, fibroblast growth factor-1, and increased lumican and collagen5a1 in the severed tendons with immunohistochemical verification. Additionally, a complex regulatory network of mechanical stimulation-mediated collagen assembly in a spatiotemporal manner was also revealed using bioinformatics analysis, wherein PI3K–Akt and HDAC4 may be the predominant signaling pathways. A wavy microgrooved surface (Y = 5.47sin(0.015x)) that biomimics tendon topography was observed to enhance the expression of collagen assembly molecules under mechanical loading, and the aforementioned pathways are particularly involved and verified with their respective inhibitors of LY-294002 and LMK-235. Furthermore, an electrospun crimped nanofiber scaffold (approximately 2 μm fiber diameter and 0.12 crimpness) was fabricated to biomimic the tenogenic niche environment; this was observed to be more effective on enhancing collagen production and assembly under mechanical stimulation. In conclusion, the synergistic effect between topographical niche and mechanical stimulation was observed to be essential for collagen assembly and maturation and should be applied to functional tendon engineering in the future. Statement of significance: In biomaterial-mediated tendon regeneration, mechanical stimulation is essential for tendon collagen assembly. However, the underlying mechanisms remain not fully defined, leading to the failure of the native-like collagen regeneration. In this study, a mechanical stimulation deprivation model of rat tendon was established to reveal the mechanisms in tendon development and define the key regulatory molecules including small leucine-rich proteoglycans, lysyl oxidase and collagen V. After ensuring the importance of biomimetic structure in tendon remodeling, crimped nanofibers were developed to verify these regulatory molecules, and demonstrated that mechanical stimulation significantly enhanced collagen assembly via PIK3 and HDAC4 pathways in biomaterial-regulated tendon regeneration. This study provides more insightful perspectives in the physiologically remodeling progression of tendon collagen and design of tendon scaffolds. Graphical abstract: Image, graphical abstract